Care for the pronated patient: an analysis of care indicators and workload - Nathália Ferreira Santos Tosti; Isabela Menezes Pinelli da Silva; Raelson Ribeiro Rodrigues; Beatriz Quirino Afonso; Fabiola Mika Tanabe; Francine Jomara Lopes (Universidade Federal do Ceará, 2024)
Objective: to analyze care indicators and workload, associating them with the quality of care provided to prone patients. Methods: a retrospective study with a convenience sample, including patients undergoing prolonged mechanical ventilation, diagnosed with COVID-19, invasive ventilation, and prone positioning. Demographic variables, information on comorbidities, ventilatory and hemodynamic status, workload using the Nursing Activities Score, quality of care indicators, diet therapy, and outcomes were collected. Results: 71 patients were evaluated; 55 (77.5%) were men, with a mean age of 65.5 years; 44 (62%) had cardiovascular diseases and 46 (62%) with metabolic diseases; 69 (97.2%) had severe hypoxemia and 52 (73.2%) used vasoactive drugs. The average Nursing Activities Score was 92.2 points; 67 (94.4%) did not reach the calorie/protein target, 47 (66.2%) developed ventilator-associated pneumonia, and 38 (53.5%) pressure injuries; 17 (23.9%) died. Conclusion: there was no statistical correlation between the worsening of care indicators and the increase in workload, although this was high at all the times studied. Contributions to practice: the high workload was related to adverse outcomes, demonstrating a relationship with the severity of the patients studied.